REKAYASA GEOMEDIS PEMANFAATAN PASIR PANTAI DI PANTAI PARANGRITIS DAN SEKITARNYA, KECAMATAN KRETEK KABUPATEN BANTUL DAERAH ISTIMEWA YOGYAKARTA - Rakhman, Arie Noor (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
This research aims to utilize sand in Parangtritis Beach, Parangtritis Subdistrict, Kretek, Bantul regency, Yogyakarta Special Region. Utilization of sand with geomedical engineering as means therapy for valuable health sand and applicable scientific. The method used in the form of field data capture characteristic properties of sand to determine the effect of the physical properties of the sand to the sand as a medium utilizing health therapy, include: color, grain size, dust properties, mineral composition, geology and inundated the following conditions as the controller. Primary data field is supported by the analysis of laboratory data in the form of grain size distribution, density, magnetic properties, and secondary data relating to the application of sand therapy information. Composition of magnetic minerals (average 66.20%) were more abundant than non-magnetic mineral grain size and the dominance of fine-sized sand (0.425 to 0.075 mm) affects the temperature of radiant heat on the sand (41.4 to 42 Â°C). Utilization of hot sand is recommended for optimal therapy performed at 16:00 to 18:00 pm with sunny weather conditions. Application using a combination therapy of Egypt model and Tembolor Beach, Lombok. Sand therapy by using a parabolic sand dunes can be applied with local wisdom of the area. Sand retrieval can be done by reusing the small scale and limited. Barchan sand dune land use is not recommended in order to preserve its existence.